Carboplatin-Pemetrexed in Treatment of Patients with Recurrent/Metastatic Cancers of the Head and Neck; Superior Outcomes in Oropharyngeal Primaries - Malhotra, Binu; Bellile, Emily Light; Nguyen, Nghia Pham Trung; Fung, Vicki Kay; Slack, Matthew; Bilich, Rebecca; Papagerakis, Silvana; Worden, Francis (Frontiers in Oncology, 2015)
Background: Platinum-based therapy in combination with 5-fluorouracil with cetuximab has shown the best survival in pts with recurrent/metastatic squamous cell carcinoma of the head and neck (R/M SCCHN). The purpose of this study is to evaluate the efficacy and tolerability of carboplatin, pemetrexed and to assess differential outcomes in patients with oropharyngeal primary and HPV related disease. Patients and Methods: The charts of consecutive patients with R/M SCCHN were reviewed. All patients receiving at least one cycle of the two-drug regimen (pemetrexed 500 mg/m2, carboplatin area under the curve of five intravenously), were included for assessment of response, safety, toxicity, and survival. Results: A total of 86 patients received this regimen between January 2008 and December 2012, of which, 63 were included in this analysis. Forty-one percent (26) of the patients had cancers of the oropharynx, and of those, 50% had HPV-positive disease, 32% (20) had cancers of the larynx, and 24% (15) of the oral cavity. Median number of cycles administered was 4 (range 1–14 cycles) with 50% of the patients receiving four or more cycles. Half the patients achieved stable disease as their best response, 8% (5) attained a partial response, 24% progressed on therapy, and the remaining patients (12) could not have their response assessed. On the basis of Kaplan–Meier analysis, median progression-free survival (PFS) was 5.1 months (95% CI 3.2, 6.2) and median overall survival (OS) was 9.4 months (95% CI 4.3, 13.1). Among pts with oropharyngeal primary (n = 26), median PFS was 6.4 months (95% CI 2.8, 7.9) and median OS was 16.6 months (95% CI 9.6, 19.5). Among HPV+ pts (n = 13), median PFS was 7.0 months (95% CI 4.8, ne) and median OS was 17.1 months (95% CI 11.2, 21.7). Conclusion: Combination carboplatin-pemetrexed is an effective and well-tolerated treatment, associated with a median PFS of 5.1 months and a clinical benefit in at least 57% of the patients treated.